COMMUNITY EDUCATION IN REDUCING THE RISK OF DIMENHYDRINATE MISUSE AS A SEDATIVE-HYPNOTIC IN LAMASI VILLAGE IN 2024 - Nurvianthi, Riska Yuli; Asmal, Adhitama; Djafar, Tanwir; Parinding, Indah Purnamasari; Wahyuddin (The Health Researcher's Journal, 2025)
The misuse of dimenhydrinate as a sedative-hypnotic can pose serious health risks. Dimenhydrinate, which is commonly used to prevent nausea and dizziness due to motion sickness, is often misused as a sleep aid. This study aims to educate the community of Lamasi Village about the risks of dimenhydrinate misuse and to enhance their understanding of the safe use of this drug. Using a quasi-experimental method with quantitative analysis, this study involved 30 respondents selected through purposive sampling. Data was collected using pre-test and post-test questionnaires via a door-to-door method. The results show a significant improvement in the community's understanding and compliance after the educational intervention. The average pre-test attitude score increased from 8.10 to 9.83, and the compliance score increased from 17.07 to 23.90. The education provided proved effective in reducing the misuse of dimenhydrinate and improving the community’s understanding of its risks.